Thermo-physiological comfort of soft-shell back protectors under controlled environmental conditions. (September 2016) - Dotti, Francesca; Ferri, Ada; Moncalero, Matteo; Colonna, Martino
Abstract: The aim of the study was to investigate thermo-physiological comfort of three back protectors identifying design features affecting heat loss and moisture management. Five volunteers tested the back protectors in a climatic chamber during an intermittent physical activity. Heart rate, average skin temperature, sweat production, microclimate temperature and humidity have been monitored during the test. The sources of heat losses have been identified using infrared thermography and the participants answered a questionnaire to express their subjective sensations associated with their thermo-physiological condition. The results have shown that locally torso skin temperature and microclimate depended on the type of back protector, whose design allowed different extent of perspiration and thermal insulation. Coupling physiological measurements with the questionnaire, it was found that overall comfort was dependent more on skin wetness than skin temperature: the participants preferred the back protector with the highest level of ventilation through the shell and the lowest level of microclimate humidity. Highlights: A method for thermo-physiological comfort assessment of back-protectors is proposed. Microclimate temperature and humidity under back-protector shells grow very fast. The presence of a vest in back-protector design affects thermal comfort. Ventilation through the soft foam shell plays a primary role in thermal comfort.